Review of the contributions of PIM-funded research on resource tenure and governance to and program decision making - Andersson, Krister; Emmelhainz, Roger (International Food Policy Research Institute, 2021)
The purpose of this review is to assess the extent to which the research outputs of Flagship 5 of the CGIAR Research Program on Policies, Institutions, and Markets (PIM5) have been used to inform decisions and behaviors of representatives of government organizations, development agencies, researchers, donors, private firms, nongovernment organizations, and other users. The review addresses seven questions: 1. Who uses the outputs of PIM5, including general publications, journal articles, briefs, and other products? 2. Who uses the tools and games created and disseminated by the Flagship researchers? 3. Who attends the outreach events and capacity-building workshops organized by researchers involved in the Flagship? 4. How are the research outputs being used? What policies, programs, and strategies have been informed, and how? 5. For selected cases, what is the research-to-uptake process and how we can learn from it? 6. What are the key cases and impact pathways identified, and what can we learn from them? What are the promising pathways that we should explore further in the final 18 months of the program? 7. What are the gaps and missed opportunities for impact that we should explore in the final months of the program, or that should be considered in the One CGIAR? To address these questions, the review relied on bibliographic references; document download data; personal interviews; focus group discussions; and three different online surveys targeting researchers and their partners, as well as different types of end users. We used both quantitative and qualitative techniques to analyze these data. In this summary, we selectively discuss the review’s most important findings and recommendations.